Hemolytic activity of Sea Anemone Aiptasia Pallida (Cnidaria: Actiniaria: Actiniidae) from Costa Rica - Córdoba-Chávez, Adriana (2017)
The Cnidaria phylum includes organisms that are among the most venomous animals. More than 32 species of sea anemones have been reported to produce lethal cytolytic peptides and proteins. This study was designed to evaluate the hemolytic activity on the crude extract of the sea anemone Aiptasia pallida. The anemone was collected, minced, homogenized and then centrifuged. Functional characterization of the crude extract was evaluated by hemolytic activity (HA) against human red blood cells. Interestingly, the HA results showed no lysis of the cells, but absorbance increased in function of time. The crude extract revealed the existence of proteins band around 30 kDa by SDS-PAGE, no actinoporin band was found in A. pallida. These results could be associated with a sub-lytic concentration of other protein family which is altering osmotic equilibrium and changing cells volume, with no lethal effect at the concentrations tested.